Gertrude Stein and the making of Jewish modernism - Feinstein, Amy (University Press of Florida, 2020)
"Challenging the assumption that modernist writer Gertrude Stein seldom integrated her Jewish identity and heritage into her work, this book uncovers Stein's constant and varied writing about Jewish topics throughout her career. Amy Feinstein argues that Judaism was central to Stein's ideas about modernity, showing how Stein connects the modernist era to the Jewish experience"--